Competition laws, ownership, and corporate social responsibility - Ding, Wenzhi; Levine, Ross; Lin, Chen; Xie, Wensi (Journal of International Business Studies, 2022)
Different theories offer different predictions of the impact of competition on corporate social responsibility (CSR). The stakeholder value and product differentiation theories hold that intensifying competition spurs firms to increase corporate social responsibility (CSR) to strengthen relationships with non-shareholder stakeholders (e.g., workers, suppliers, customers, and local communities) and differentiate their products to gain pricing power. However, textbook theories of the firm imply that competition spurs firms to focus on short-term survival and forgo investments that pay off in the long run, such as CSR. The purpose of this paper is to evaluate these competing hypotheses. Methodologically, we use a large sample of firm-level data on CSR and panel data on competition laws across 47 countries from 2002 to 2015 and employ multivariate regressions. We find evidence consistent with the stakeholder value and product differentiation theories: intensifying competition laws leads firms to increase their CSR activities, and the CSR-enhancing effects of competition vary across (a) firms with different institutional owners, controlling owners, industry structures, and financing constraints, and (b) countries with different social attitudes toward CSR in ways consistent with the stakeholder value and product differentiation theories. The results imply that firms use CSR, at least partially, as a profit-maximizing strategy.